2018
DOI: 10.3389/fpsyg.2018.00052
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Facial Mimicry: Simultaneous Measurements of EMG and BOLD Responses during Perception of Dynamic Compared to Static Facial Expressions

Abstract: Facial mimicry (FM) is an automatic response to imitate the facial expressions of others. However, neural correlates of the phenomenon are as yet not well established. We investigated this issue using simultaneously recorded EMG and BOLD signals during perception of dynamic and static emotional facial expressions of happiness and anger. During display presentations, BOLD signals and zygomaticus major (ZM), corrugator supercilii (CS) and orbicularis oculi (OO) EMG responses were recorded simultaneously from 46 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
56
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 87 publications
13
56
0
2
Order By: Relevance
“…For example, three previous studies (Badzakova‐Trajkov et al, ; Fox et al, ; Sato et al, ) indicated that observation of dynamic facial expressions activated the dorsomedial prefrontal cortex (dmPFC), which could be involved in attributing the intentions and other mental states from the faces of others (Frith & Frith, ). One possible reason for these inconsistent findings is sample size, which was less than 30 in all previous individual experiments with only a few exceptions (Badzakova‐Trajkov et al, ; Kessler et al, ; Rymarczyk et al, ), because studies involving small sample sizes may have low statistical power and a reduced chance of detecting effects (Button et al, ). This issue could be relevant even to meta‐analyses (Arsalidou et al, ; Zinchenko et al, ) because these studies employed coordinate‐based meta‐analytical methods, which assess the convergence of the locations of activation foci reported in individual studies and have difficulty detecting small effects with underpowered individual studies (Acar, Seurinck, Eickhoff, & Moerkerke, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, three previous studies (Badzakova‐Trajkov et al, ; Fox et al, ; Sato et al, ) indicated that observation of dynamic facial expressions activated the dorsomedial prefrontal cortex (dmPFC), which could be involved in attributing the intentions and other mental states from the faces of others (Frith & Frith, ). One possible reason for these inconsistent findings is sample size, which was less than 30 in all previous individual experiments with only a few exceptions (Badzakova‐Trajkov et al, ; Kessler et al, ; Rymarczyk et al, ), because studies involving small sample sizes may have low statistical power and a reduced chance of detecting effects (Button et al, ). This issue could be relevant even to meta‐analyses (Arsalidou et al, ; Zinchenko et al, ) because these studies employed coordinate‐based meta‐analytical methods, which assess the convergence of the locations of activation foci reported in individual studies and have difficulty detecting small effects with underpowered individual studies (Acar, Seurinck, Eickhoff, & Moerkerke, ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of neuroimaging studies using functional magnetic resonance imaging (fMRI) and positron emission tomography have been performed to gain insight into the neural mechanisms underlying the processing of dynamic facial expressions (Arnold, Iaria, & Goghari, ; Arsalidou, Morris, & Taylor, ; Badzakova‐Trajkov, Haberling, Roberts, & Corballis, ; De Winter et al, ; Faivre, Charron, Roux, Lehéricy, & Kouider, ; Foley, Rippon, Thai, Longe, & Senior, ; Fox, Iaria, & Barton, ; Furl, Henson, Friston, & Calder, ; Grosbras & Paus, ; Johnston, Mayes, Hughes, & Young, ; Kessler et al, ; Kilts, Egan, Gideon, Ely, & Hoffman, ; Kret, Pichon, Grezes, & de Gelder, ; LaBar, Crupain, Voyvodic, & McCarthy, ; Pelphrey, Morris, McCarthy, & Labar, ; Pentón et al, ; Polosecki et al, ; Rahko et al, ; Reinl & Bartles, ; Rymarczyk, Zurawski, Jankowiak‐Siuda, & Szatkowska, ; Sato, Kochiyama, Uono, & Yoshikawa, ; Sato, Kochiyama, Yoshikawa, Naito, & Matsumura, ; Sato, Toichi, Uono, & Kochiyama, ; Schobert, Corradi‐Dell'Acqua, Frühholz, van der Zwaag, & Vuilleumier, ; Schultz, Brockhaus, Bülthoff, & Pilz, ; Schultz & Pilz, ; Trautmann, Fehr, & Herrmann, ; van der Gaag, Minderaa, & Keysers, ; for reviews, see Arsalidou et al, ; Zinchenko, Yaple, & Arsalidou, ). These studies contrasted brain activation during observation of dynamic emotional facial expressions with that during observation of control stimuli matched for visual motion or form with the dynamic expressions, such as dynamic mosaics, dynamic objects, nonemotional facial movements, and static emotional facial expressions.…”
Section: Introductionmentioning
confidence: 99%
“…Within this theoretical framework, facial mimicry has been conceived as linked to an internal simulation process that the observer would spontaneously put in place during the observation of others' facial expressions and that, ultimately, would support their recognition [27][28][29][30][31]. In line with this proposal, neuroimaging techniques have shown that (pre)motor and somatosensory regions representing the face are active during the perception of emotional face [32][33][34][35], and neural activity in these regions correlates with the degree of facial mimicry [36][37][38]. Moreover, damage to, or transcranial magnetic stimulation (TMS) interference with, the face representations in motor and somatosensory areas disrupts facial mimicry and impairs the recognition and interpretation of emotional expressions [39][40][41][42][43][44] (see also [45]).…”
Section: Introductionmentioning
confidence: 99%
“…Previous neuroimaging research has generated some support for these predictions but this evidence has faced technological and experimental constraints. Participants have viewed emotional images and faces while undergoing combined fMRI scanning and facial EMG recording (Heller et al, 2011;Likowski et al, 2012;Rymarczyk et al, 2018). However, technological constraints have previously prevented researchers from directly relating time-locked brain and facial muscle activity on a trial-by-trial basis.…”
Section: Discussionmentioning
confidence: 99%
“…Several research teams have recorded targets' brain and facial muscle activity by combining fMRI with facial electromyography (EMG). Targets in these studies produced facial EMG responses, and recruited brain structures broadly associated with experiencing emotion and mentalizing, when they viewed emotional images and faces (Heller et al, 2011;Likowski et al, 2012;Rymarczyk et al, 2018). Although revealing, this work does not isolate brain activity that "tracks" simultaneous facial movement on a trial-by-trial basis.…”
mentioning
confidence: 87%